2018
DOI: 10.1016/j.jalz.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Altered bile acid profile in mild cognitive impairment and Alzheimer's disease: Relationship to neuroimaging and CSF biomarkers

Abstract: Introduction: Bile acids (BAs) are the end products of cholesterol metabolism produced by human and gut microbiome co-metabolism. Recent evidence suggests gut microbiota influence pathological features of Alzheimer’s disease (AD) including neuroinflammation and amyloid-β deposition. Method: Serum levels of 20 primary and secondary BA metabolites from the AD Neuroimaging Initiative (n=1562) were measured using targeted metabolomic profiling. We assessed the association of BAs with the “A/T/N” (Amyloid, Tau an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
154
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 240 publications
(160 citation statements)
references
References 86 publications
6
154
0
Order By: Relevance
“…The authors conclude that their results "support the possibility that impaired hepatic A␤ degradation could be a factor contributing to increased brain A␤ accumulation and AD" [55]. In addition, serum-based bile acid metabolites are associated with AD biomarkers, providing further evidence that bile acid pathways play a role in AD pathophysiology [56].…”
Section: Clearancementioning
confidence: 85%
“…The authors conclude that their results "support the possibility that impaired hepatic A␤ degradation could be a factor contributing to increased brain A␤ accumulation and AD" [55]. In addition, serum-based bile acid metabolites are associated with AD biomarkers, providing further evidence that bile acid pathways play a role in AD pathophysiology [56].…”
Section: Clearancementioning
confidence: 85%
“…Additionally, we saw negative associations of episodic memory and global cognition with the ratio of both conjugated and unconjugated deoxycholic acid (DCA) to cholic acid (CA) and conjugated lithocholic acid (LCA) to CDCA. Those ratios represent dihydroxylation of primary bile acids (CA and CDCA) by gut bacteria and were previously reported to be negatively associated with cognition 54 and atrophy, and brain glucose metabolism in AD 55 .…”
Section: Discussionmentioning
confidence: 98%
“…Bile acids and steroid are also linked to the regulation of glucose and insulin metabolism 13 , energy metabolism and inflammation 14,15 and implicated in the pathogenesis of type 2 diabetes and metabolic syndrome 16 . Previous studies reported associations between AD, cognition and plasma levels of oxylipins 17 , bile acids 18,19 and steroids 20,21 . However, broader simultaneous assessments of lipid mediator profiles in the context of mild cognitive impairment have not been conducted to date.…”
Section: Introductionmentioning
confidence: 97%
“…Liquid chromatography-mass spectrometry- (LC-MS) based metabolomics is a powerful tool to profile metabolite changes. It has been utilized to decipher metabolic reprogramming in many types of disease including neurodegenerative disorders [ 12 , 15 , 16 ]. Previous studies indicated the involvement of oxidative stress and dyshomeostasis in metabolism of catecholamine, tryptophan and caffeine in PD [ 3 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%